How punctuality affects on time performance in the aviation sector: Pakistan International Airline - Khan, Hassaan Saleem (2018)
Punctuality has become increasingly important and gained attention over the last few years. This importance has been attained due to the level of role it has in the economics of the aviation industry. Punctuality is not just a sound indicator of performance rather it helps airline to be in the blue ocean. Pakistan International Airlines (PIA) faces stiff competition from international and domestic airlines on various routes globally. Due to fierce competition, global aviation industry rules and some inward factors, for example, human resource issues of over staffing, de-motivated employees, mismanagement of assets both in the case of manpower and other assets, old and shortage of fleet, corruption and absence of accountability have resulted in PIA confronting a profound financial crisis. It is losing its market share both domestically and globally.